Stellar Absorption Line Analysis of Local Star-forming Galaxies: The Relation between Stellar Mass, Metallicity, Dust Attenuation, and Star Formation Rate - Zahid, H. Jabran; al., et (2017)
We analyze the optical continuum of star-forming galaxies in the Sloan Digital Sky Survey by fitting stacked spectra with stellar population synthesis models to investigate the relation between stellar mass, stellar metallicity, dust attenuation, and star formation rate. We fit models calculated with star formation and chemical evolution histories that are derived empirically from multi-epoch observations of the stellar mass–star formation rate and the stellar mass–gas-phase metallicity relations, respectively. We also fit linear combinations of single-burst models with a range of metallicities and ages. Star formation and chemical evolution histories are unconstrained for these models. The stellar mass–stellar metallicity relations obtained from the two methods agree with the relation measured from individual supergiant stars in nearby galaxies. These relations are also consistent with the relation obtained from emission-line analysis of gas-phase metallicity after accounting for systematic offsets in the gas-phase metallicity. We measure dust attenuation of the stellar continuum and show that its dependence on stellar mass and star formation rate is consistent with previously reported results derived from nebular emission lines. However, stellar continuum attenuation is smaller than nebular emission line attenuation. The continuum-to-nebular attenuation ratio depends on stellar mass and is smaller in more massive galaxies. Our consistent analysis of stellar continuum and nebular emission lines paves the way for a comprehensive investigation of stellar metallicities of star-forming and quiescent galaxies.